Perancangan UI/UX pada Penjualan Produk Bodycare Dermanifest Menggunakan Metode Design Thinking - Putu Sanisa Pascaline; Ari Hendarno; Fariani Hermin Indiyah (J-KOMA : Jurnal Ilmu Komputer dan Aplikasi, 2023)
The digitalization trend has driven many companies to transition to websites, including those in the bodycare industry, due to challenges in product inventory, manual ordering processes, and fierce competition in e-commerce. One such affected entity is Dermanifest. Dermanifest is a bodycare product sales company committed to enhancing customer service through innovation. Throughout its business journey, Dermanifest has faced difficulties in accessing product information and interacting with sellers. To address these issues, a UI/UX design was developed using the design thinking method to meet user needs effectively. The process involved five stages: Empathize through interviews with Customers and Admins, Define to establish key problems, Ideate for solution generation, and Prototype and Test stages. Effective UI/UX design was crucial to developing a website that meets both business internal needs and customer requirements. This research successfully produced two UI/UX prototypes—low-fidelity and high-fidelity—with 25 specific pages for Dermanifest Admin and 15 pages for Customers. These designs received an Excellent rating for all aspects in achieving Dermanifest users' goals based on User Experience Questionnaire (UEQ) evaluations. Subsequently, Usability Testing was conducted using the Maze platform, resulting in a score of 87.2 out of 100 for the Admin interface. In conclusion, employing a user-centered approach, the UI/UX design effectively addressed Dermanifest's challenges and is poised for further implementation. Keywords: Design thinking, UI/UX, Dermanifest, UEQ, Usability Testing, E-commerce, Prototype.